THE IMPACT OF TARIFF REDUCTIONS IN TAIWAN AND INDONESIA’S REQUEST-OFFER SCHEMES ON INDONESIA'S SECTORAL ECONOMY: GTAP SIMULATION VERSION 9 - Betrix Silitonga (Politeknik Negeri Ambon, 2026)
Introduction: The trade field between Indonesia and Taiwan, namely cooperation under product tariffs, is increasingly expanding across various sectors. Methods: This study analyzes the impact of Taiwan's and Indonesia's request-offer schemes on Indonesia’s sectoral economic performance, including exports, imports, outputs, and employment opportunities, using GTAP Simulation Version 9.Results: In the GTAP simulation version 9, textiles experienced the largest increases in exports and imports, while non-food products experienced the most significant increase in output. Food products, fishing, and textiles experienced the largest increases in labour demand. Conclusion and Suggestion: Most of Indonesia's bilateral economic and trade cooperation with Taiwan has had a positive influence on Indonesia's sectoral economy. Through their respective roles, including those of the government, stakeholders, companies, investors, and business actors, they can help accelerate Indonesia's sectoral economic growth in the future while maintaining national interests. It is necessary to improve the quality of Indonesia's exports and output through improving the quality of domestic products and empowering Indonesian workers in Taiwan to be more skilled and understand their rights and obligations, as well as providing optimal assistance to strengthen human rights for all Indonesian workers. Keywords: Optimistic Scenario, Pessimistic Scenario, Request-Offer Scheme, Sectoral Economics, Tariff Reduction